Thermogravimetric data suggest synergy between different organic fractions and clay in soil structure formation - Ivan Šimkovic; Andrej Hrabovský; Adela Joanna Hamerníková; Silvia Ihnačáková; Pavel Dlapa (Geoderma)
Although it has been recognized that soil structure formation affects soil organic carbon (SOC) sequestration, experimental data elucidating the relation between mechanical properties of soil structure and soil organic matter (SOM) stability are lacking. This study assesses the link between aggregate stability and SOM stability in lowland and hilly land soils of Central Europe. Overall, 39 topsoil samples were taken. Besides determining basic properties and nutrient availability, stability of soil aggregates was quantified using wet sieving (WS) and rainfall simulation (RS) procedures. The samples were analyzed by thermogravimetry and differential scanning calorimetry (TG-DSC). Besides significant correlations with basic soil properties and contents of selected nutrients, the aggregate stability data were linked to thermal processes, such as water desorption and SOM degradation. The RS values were significantly correlated (r > 0.7, p < 0.001) with the rate of water desorption (T < 200 °C) and SOM degradation (200 – 570 °C). Observed correlation pattern, with multiple maxima, suggests that aggregate stability is supported by clay and several SOM fractions, each showing different thermal stability. Significant correlations observed bellow 200 °C indicate that properties controlling soil specific surface area (SOM and clay) are important also for the aggregate stability. The 78 % of the variance observed in aggregate stability testing was explained by multilinear regression using weight loss rates recorded at selected temperatures (80, 130, 248, 401 and 455 °C) as predictors. We observed different relations between exothermic energy values, soil aggregate stability and thermal stability of SOM (SOC). Exothermic heat flux normalized with respect to SOC mass (energy density) indicates presence of stable organic fraction, as it showed correlation also with clay, which has positive effect on SOC stabilization. This is in line with the positive correlation between SOC energy density and aggregate stability. On contrary, normalizing the heat with respect to SOM mass indicates the content of labile organic components, as the correlations with clay or aggregate stability were insignificant. The TG-DSC data revealed that hilly land soils are depleted in fresh organic material, which is due to their genesis and the erosion intensified by tillage.